2017
DOI: 10.1016/j.chroma.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Multisegment injections improve peptide identification rates in capillary zone electrophoresis-based bottom-up proteomics

Abstract: While capillary zone electrophoresis (CZE) provides dramatically improved numbers of peptide identifications compared with reversed-phase chromatography for bottom-up proteomics of mass limited samples, CZE inevitably produces lower numbers of peptide identifications than RPLC for larger samples. One reason for this poorer performance is the dead time between injection of samples and subsequent appearance of the fastest moving component. This dead time is typically 25% of the separation window in CZE, but is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Boley et al. showed a doubling in the peptide identification rate . Using such an approach in an offline two‐dimensional RPLC‐CZE‐MS system, Faserl et al.…”
Section: Analytical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boley et al. showed a doubling in the peptide identification rate . Using such an approach in an offline two‐dimensional RPLC‐CZE‐MS system, Faserl et al.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Sequential injection of samples can increase the throughput of CE-MS by lowering dead times between runs. Boley et al showed a doubling in the peptide identification rate [58]. Using such an approach in an offline two-dimensional RPLC-CZE-MS system, Faserl et al identified 62 000 peptides, representing 6100 proteins in a 12.5 h run by sequential injection of RPLC fractions every 10 min [59].…”
Section: Bottom-up Proteomicsmentioning
confidence: 99%
“…Thereafter, it was developed to solve the problem of lacking IS in protein analysis via successive injections of the standard protein at a known concentration followed by the sample to be quantified . Along with the successful applications in metabolic profiling and bottom‐up proteomics , MSI–CE–MS has been accepted as a very efficient approach for increasing the throughput of metabolomics and proteomics analysis .…”
Section: Introductionmentioning
confidence: 99%
“…Very recently Boley et al. performed three sequential injections of a yeast proteome digest . However, since both groups injected the same sample multiple times the increase in proteome coverage is limited.…”
mentioning
confidence: 99%
“…[14] Very recently Boley et al performed three sequential injections of a yeast proteome digest. [15] However, since both groups injected the same sample multiple times the increase in proteome coverage is limited. To evaluate the sequential injection CE-MS method for its applicability in proteomics research we extracted and digested whole proteins from human lymphoblastic T-cells.…”
mentioning
confidence: 99%